The Battle of the Atlantic - Hughes, Terry, 1933-; Costello, John, 1943- (New York : Dial Press/J. Wade, 1977)
THE FIRST COMPLETE, THOROUGHLY DOCUMENTED ACCOUNT OF THE PIVOTAL CAMPAIGN OF WORLD WAR II--THE GERMAN ATTEMPT TO SEVER ALLIED SUPPLY LINES IN THE ATLANTIC.
Total Germany! -- The power of audacity -- The acme of villainy -- The sinister trance -- A certain eventuality -- The 'happy time' -- Siege by sea and air -- A time of trouble -- Dig harder to beat the U-boats -- Clash of Titans -- Charter for survival -- Damn the torpedoes-full speed ahead! -- The American shooting season -- Winning the war with ships -- The bloody winter of '43 -- Race against time.
Includes bibliographical references (pages 310-311) and index.
Keywords: World War, 1939-1945 -- Campaigns -- Atlantic Ocean; Ships -- 1930-1950.; Atlantic Ocean; Books